PELAKSANAAN SUPERVISI OLEH KEPALA TK di KECAMATAN PADANG TIMUR KOTA PADANG - Yusnani , (Universitas Negeri Padang, 2013)
This study aims to determine teachers' Supervise the implementation of the principal. This is a descriptive study. The population in this study were taken in two stages. population is 151 teachers from 32 schools. District are in supervise the implementation of the principle with an average score overall was 2.39. From the research it can be said that Supervise the implementation of the principal kecamatan Padang Timur Padang city isn’t good. Key word; Supervise the implementation of the principal